2014
DOI: 10.1097/nmd.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition and Levels of Personality Organization in Patients With Somatoform Disorders

Abstract: Social cognition and its association with level of personality organization (PO) were examined in 163 patients with severe somatoform disorders (SFDs) and 151 psychiatric (PSA) control patients. Social cognition was measured with the Social Cognition and Object Relations Scale, which assessed both affective and cognitive facets of social cognition. Levels of PO were assessed using theory-driven profiles of the Dutch Short Form of the Minnesota Multiphasic Personality Inventory (MMPI). The SFD patients exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…The higher level of self-reported social competence and sociability found in the present study contrasts with previous findings of Koelen et al [48], who studied social cognition among SFD-patients in an indirect way using the Social Cognition and Object Relations Scale (SCORS) [58,59]. This scale assesses cognitive (complexity of inner representations of self and others; understanding of social causality) and affective aspects of social cognition (emotional investment in relationships and affect tone of relationships).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…The higher level of self-reported social competence and sociability found in the present study contrasts with previous findings of Koelen et al [48], who studied social cognition among SFD-patients in an indirect way using the Social Cognition and Object Relations Scale (SCORS) [58,59]. This scale assesses cognitive (complexity of inner representations of self and others; understanding of social causality) and affective aspects of social cognition (emotional investment in relationships and affect tone of relationships).…”
Section: Discussioncontrasting
confidence: 56%
“…Although the absolute number of patients with this type of PO is relatively small in this study, it suggests that there might be a sub-group of SFD-patients with a high level of structural vulnerability and low anxiety tolerance. In this subgroup of vulnerable SFD-patients with PPO, somatization may have an integration preserving function, as had been suggested [48] and has recently been found [49].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Similarly, in another study, these authors found that individuals with T1D with avoidant attachment showed poorer treatment adherence than those with secure or ambivalent attachment styles (Ciechanowksi et al, 2001). Furthermore, studies converge to suggest that chronic somatic disorders may lead to serious impairments and distortions in (embodied) mentalizing (Luyten and Fonagy, 2016;Fonagy, 2012, 2013;Koelen, Eurelings-Bontekoe, van Broeckhuysen-Kloth, Snellen, and Luyten, 2014;Schönenberg et al, 2014;Malberg, 2013). Such distortions are, for instance, expressed in a tendency to make catastrophic attributions in response to bodily sensations, in the incapacity to reappraise threatening situations, and in the rigid misinterpretation of others' behaviors.…”
Section: Figure 1 T1d Stress and Attachment Mentalizingmentioning
confidence: 99%